Chinese justice : civil dispute resolution in contemporary China - Gallagher, Mary Elizabeth , 1969-; Woo, Margaret Y. K. (Cambridge University Press, 2011)
Analyzes whether China's thirty years of legal reform have taken root in Chinese society by examining how ordinary citizens are using the legal system